Effect of Anti-Riboflavin factor in the residues of the tomato paste industry on the Physiological and Biochemical traits of broilers - Rzuqi, Maha A. (The Iraqi Journal of Veterinary Medicine, 2018)
The aim of this study was to investigate the effect of anti-riboflavin factor in dried tomato seed meal on some physiological and biochemical traits of broiler. This study was conducted at the poultry farm of the Veterinary Medicine College at Baghdad University. A total of (150 broiler chicks) were used in this study for 56 days. The chicks were randomly distributed into five treated groups, 30 chicks for each period. Chicks at the age of 3 days were fed Ad libitum during the whole period and dried tomato seed meal was added to the diets of birds at the concentration of 0, 2.5, 5, 7.5 and 10% respectively. The results revealed that dietary supplementation with different levels of dried tomato seed meal resulted in a significant (P≤0.05) improvement regarding physiological and health traits. Also, adding 10.0% of dried tomato seed meal was the best among the other dietary supplementation levels of tomato seed meal. No signs of riboflavin deficiency appeared on broiler chicks.